Muslim women's experiences of domestic violence in the Nelson Mandela metropole: a qualitative study - Razia Nordien; Nicky Alpaslan; Blanche Pretorius (AOSIS, 2003)
This article provides a reflection on the experiences of Muslim women with regard to domestic violence. Opsomming Hierdie artikel werp 'n blik op Moslemvroue se ervarings van huweliksgeweld. *Please note: This is a reduced version of the abstract. Please refer to PDF for full text.